PEDAGOGICAL CHALLENGES IN TEACHING ENGLISH FOR YOUNG LEARNERS (TEYL) AT AL-ULUM ISLAMIC SCHOOL PEKANBARU - Farikha Alifia Ruqoyah; Afrianto Daud; Hadriana (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2026)
This research aimed to investigate the pedagogical challenges faced by English teachers in Teaching English for Young Learners (TEYL) in the context of an Islamic school. Qualitative research was employed with three English teachers from Grades 1, 3, and 6 at Al-Ulum Islamic School, Pekanbaru. Data were collected through semi-structured interviews and classroom observations, and then analyzed thematically. The findings showed that they encountered various challenges, including differences in students’ abilities within a class, limited instructional time, heavy teaching workloads, lack of resources and professional training, difficulty in maintaining students’ motivation alongside participation, as well as curriculum-related obstacles. To address these issues, they adjusted their teaching by differentiating materials and activities, applying varied strategies and media, positioning stronger students as peer models, and modifying assessment practices to suit learners’ abilities. The implications that can be given from this research emphasize the importance of providing professional development opportunities in TEYL and also highlight the need for stronger institutional support for English teaching in Islamic school contexts.